Full electrothermal physically-based modeling of the power diode using PSPICE. (February 2016) - Shaker, Ahmed; Abouelatta, Mohamed; El-Banna, Mohammed; Ossaimee, Mahmoud; Zekry, Abdelhalim
Highlights: An improved electrothermal model of power diode has been developed. The model is based on the numerical solution of the ADE for all injection levels. It is capable in tracing the electrical and thermal effects including self-heating. Transient thermal responses are verified for repetitive and single pulse modes. The results show that the model is suitable for full electrothermal simulations. Abstract: In this paper, an improved electrothermal model of power diode has been developed. This improved model is based on the numerical solution of the ambipolar diffusion equation (ADE) for all levels of injection instead of high level injection only as usually encountered. The main local physical effects are taken into consideration. The proposed model is capable in tracing the electrical and thermal effects including self-heating of the device under practical operation (with current density levels ranging from few mA/cm 2 to few thousands of A/cm 2 ). The model has been validated against measurements and other models showing close agreement for different circuits (DC forward characteristics, turn-on and turn-off) and different temperatures (over the range of 25–125 °C). The comparison shows that the presented model is superior in predicting the main circuit parameters needed for power electronic design. The transient thermal responses are demonstrated for both repetitive and single pulse modes. The presented results show that our model is suitable for full electrothermal simulations of power electronic circuits.